(untitled) (Biological Sciences - PJSIR, 2004)
A two-stage sequential extraction procedure for the speciation of zinc and lead has been applied to surface water randomly collected from three sites in Abegede Creek, Ijora and Lagos. The determination of the labile and non-labile metals species was carried out by flame atomic absorption spectrophotometry (FAAS). The mean values of non-labile zinc and lead concentrations from the three sites, A, B and C are 0.54 ± 0.25 mg/l; 0.55 ± 0.26 mg/l; 1.13 + 0.76 mg/l, respectively for zinc and 0.13 ± 0.09; mg/l, 0.17 ± 0.07 mg/l; 0.42 ± 0.23 mg/l respectively for lead. These are higher than for the labile species in the three sites; 0.14 ± 0.07 mg/l; 0.21± 0.22 mg/l; 0.73 ± 0.82 mg/l, respectively for zinc and ND; 0.02 ± 0.04 mg/l; 0.16 ± 0.22 mg/l, respectively for lead. The statistical analysis of variance of the distribution of zinc and lead in the three sites were estimated at 95% confidence level. The values of metals obtained were compared with Nigeria’s background values for some rivers and the World Health Organization limits for drinking water respectively and found to be generally higher especially for lead levels. The probable sources of zinc and lead in the Creek are from natural and point sources, although there could be non-point source contributions from urban run-offs and vehicular exhaust.